2019
DOI: 10.1002/hpm.2898
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing missed nursing care in public hospitals in Australia: An exploratory mixed methods study

Abstract: Summary Background Missed nursing care (MNC) is a significant health care issue that impacts on the quality of health care and patient safety. It refers to delayed or omitted aspects of nursing care (totally or partially). MNC is an under‐researched area in the Australian health care context. Objective This research sought to further explore the MNC phenomenon in the context of an acute care hospital and to identify its common elements and the factors influencing its occurrence. Design A convergent parallel mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
36
2
8

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(63 citation statements)
references
References 59 publications
4
36
2
8
Order By: Relevance
“…A recent study identified that about one‐third of the nursing staff was not satisfied with their work environment, where 17% have no confidence in the field of management and the lack of support from nursing leadership was a cause for the omission of treatment. This study concluded by reflecting on the paradox of a system that, by using a managerial approach that mainly pursues efficiency, generates lack of trust on the part of the staff towards the managerial system itself (Albsoul, FitzGerald, Finucane, & Borkoles, 2019). A crucial role, in this constant tension between organisational efficiency and meeting patients' needs, is played by the charge nurse and the nursing leaders, who constantly have to balance resources to obtain positive outcomes to achieve the effectiveness and efficiency of nursing interventions (Ingwell‐Spolan, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…A recent study identified that about one‐third of the nursing staff was not satisfied with their work environment, where 17% have no confidence in the field of management and the lack of support from nursing leadership was a cause for the omission of treatment. This study concluded by reflecting on the paradox of a system that, by using a managerial approach that mainly pursues efficiency, generates lack of trust on the part of the staff towards the managerial system itself (Albsoul, FitzGerald, Finucane, & Borkoles, 2019). A crucial role, in this constant tension between organisational efficiency and meeting patients' needs, is played by the charge nurse and the nursing leaders, who constantly have to balance resources to obtain positive outcomes to achieve the effectiveness and efficiency of nursing interventions (Ingwell‐Spolan, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Outros autores evidenciaram os problemas com a documentação do prontuário do paciente entre as causas de eventos adversos de medicação (Manias et al, 2019) A literatura reforça a importância disso, ao passo que a transferência de informações e compreensão compartilhadas são umas das principais causas de falha de comunicação entre enfermeiros e médicos extraídos de relatórios de incidentes (Elizabeth Umberfield, Amir A Ghaferi, Sarah L Krein, 2019). Não se detendo apenas a relação médico enfermeiro, problemas de omissão e atrasos na assistência de enfermagem são impactados pela transferência de informação deficiente (Albsoul et al, 2019).…”
Section: Discussionunclassified
“…Em consonância a isso, um estudo examinou as tendências de erros de medicação, em que médicos e farmacêuticos tiveram chances reduzidas de cometerem falhas em comparação com enfermeiros, a diferença entre as disciplinas se deu na frequência de interrupções e distrações no qual os enfermeiros são submetidos (Manias et al, 2019). As interrupções no fluxo de trabalho são responsáveis por atrasos e omissões na assistência em enfermagem (Albsoul et al, 2019).…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Ball J E (19) 2014 Transversal PES -NWI Recursos humanos inadequados (2.917 enfermeiros). Albsoul R (20) 2019 Exploratório Métodos mistos MISSCARE Interrupção do trabalho, gerência ausente e equipe mal relacionada (44 enfermeiros).…”
Section: Formas De Rastreio Fatores (Amostra)unclassified